2015
DOI: 10.1016/j.nmni.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pathogenicity of binary toxin–positive Clostridium difficile strains that do not produce toxins A and B

Abstract: Clostridium difficile causes antibiotic-associated diarrhoea and pseudomembranous colitis. The main virulence factors of C. difficile are the toxins A (TcdA) and B (TcdB). A third toxin, called binary toxin (CDT), can be detected in 17% to 23% of strains, but its role in human disease has not been clearly defined. We report six independent cases of patients with diarrhoea suspected of having C. difficile infection due to strains from toxinotype XI/PCR ribotype 033 or 033-like, an unusual toxinotype/PCR ribotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 30 publications
3
85
0
4
Order By: Relevance
“…CDT has been associated with more severe disease (Barbut et al, 2005), but not proven to cause disease on its own Gerding et al, 2014). While strains that produce CDT in the absence of toxins A and B have recently been linked to symptomatic CDI in immunocompromised individuals, their pathogenicity in general still remains unclear (Androga et al, 2015;Eckert et al, 2015;Grandesso et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…CDT has been associated with more severe disease (Barbut et al, 2005), but not proven to cause disease on its own Gerding et al, 2014). While strains that produce CDT in the absence of toxins A and B have recently been linked to symptomatic CDI in immunocompromised individuals, their pathogenicity in general still remains unclear (Androga et al, 2015;Eckert et al, 2015;Grandesso et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…As already mentioned above, type 244/IXb is an emerging cause of community infections in Australia (27). Toxinotype XI (all subtypes) is still rare in humans, and its role in the associated disease is debated because of the lack of toxins A and B and production of CDT only (34).…”
Section: Why Are Toxinotypes Important?mentioning
confidence: 99%
“…A further study suggested that CDT was a predictor of recurrent infection, and its presence may require longer antibiotic treatments [148]. CDT þ C. difficile strains that do not produce toxins A and B have been described in independent cases of patients with diarrhoea suspected of having CDI [149].…”
Section: Difficile Characteristics and Its Toxinsmentioning
confidence: 99%